Supramolecular Assembly of Aminoethylene‐Lipopeptide PMO Conjugates into RNA Splice‐Switching Nanomicelles. (19th September 2019) - Kuhn, Jasmin; Klein, Philipp M.; Al Danaf, Nader; Nordin, Joel Z.; Reinhard, Sören; Loy, Dominik M.; Höhn, Miriam; El Andaloussi, Samir; Lamb, Don C.; Wagner, Ernst; Aoki, Yoshitsugu; Lehto, Taavi; et al.
Abstract: Phosphorodiamidate morpholino oligomers (PMOs) are oligonucleotide analogs that can be used for therapeutic modulation of pre‐mRNA splicing. Similar to other classes of nucleic acid‐based therapeutics, PMOs require delivery systems for efficient transport to the intracellular target sites. Here, artificial peptides based on the oligo(ethylenamino) acid succinyl‐tetraethylenpentamine (Stp), hydrophobic modifications, and an azide group are presented, which are used for strain‐promoted azide‐alkyne cycloaddition conjugation with splice‐switching PMOs. By systematically varying the lead structure and formulation, it is determined that the type of contained fatty acid and supramolecular assembly have a critical impact on the delivery efficacy. A compound containing linolenic acid with three cis double bonds exhibits the highest splice‐switching activity and significantly increases functional protein expression in pLuc/705 reporter cells in vitro and after local administration in vivo. Structural and mechanistic studies reveal that the lipopeptide PMO conjugates form nanoparticles, which accelerate cellular uptake and that the content of unsaturated fatty acids enhances endosomal escape. In an in vitro Duchenne muscular dystrophy exon skipping model using H2K‐ mdx 52 dystrophic skeletal myotubes, the highly potent PMO conjugates mediate significant splice‐switching at very low nanomolar concentrations. The presented aminoethylene‐lipopeptides are thus a promising platform for the generation of PMO‐therapeutics with a favorable activity/toxicity profile. Abstract : Artificial peptides based on oligoamino acids and lipid modifications are developed for conjugation and intracellular delivery of splice‐switching phosphorodiamidate morpholino oligomers (PMOs). The lipopeptide PMO conjugates synthesized via solid‐phase synthesis and strain‐promoted azide‐alkyne cycloaddition assemble into nanomicelles with accelerated cellular uptake and enhanced splice‐switching activity.